2022
DOI: 10.3390/su142214865
|View full text |Cite
|
Sign up to set email alerts
|

A Summary Analysis of Groundwater Vulnerability to Climate Variability and Anthropic Activities in the Haouz Region, Morocco

Abstract: The Haouz aquifer is undergoing climatic aridity and anthropic pressure largely related to the agricultural sector. In this study, special attention was given to the main factors that have a direct impact on the fluctuations of the piezometric level (PL). Different statistical analyses (cross-correlations, PCA, cascading analysis) of the relationship between these factors were applied here. The results identify three distinct groundwater operating systems. The first is manifested in areas dominated by groundwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…In many parts of the world, groundwater is increasingly used for their drinkingwater supply and irrigation [2,3]. It constitutes a primary or alternative source of water, particularly during periods of drought when surface water is less frequent, which leads to water table depletion and its long-term deterioration [4]. In order to acquire more knowledge of this phenomenon, numerous authors have conducted research on groundwater drought.…”
Section: Introductionmentioning
confidence: 99%
“…In many parts of the world, groundwater is increasingly used for their drinkingwater supply and irrigation [2,3]. It constitutes a primary or alternative source of water, particularly during periods of drought when surface water is less frequent, which leads to water table depletion and its long-term deterioration [4]. In order to acquire more knowledge of this phenomenon, numerous authors have conducted research on groundwater drought.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the groundwater rose by more than 4 m in the areas adjacent to the river (Figure 2). Several other studies also established the same manner where groundwater level fluctuation based on the influence of hydraulic structure or surface water [15][16][17]. The alarming groundwater depletion situation is believed to be a constraint in the economic growth of countries with heavy dependence on surface-and groundwater usage [18].…”
Section: Introductionmentioning
confidence: 99%